2016
DOI: 10.3389/fpls.2016.01235
|View full text |Cite
|
Sign up to set email alerts
|

Garlic, from Remedy to Stimulant: Evaluation of Antifungal Potential Reveals Diversity in Phytoalexin Allicin Content among Garlic Cultivars; Allicin Containing Aqueous Garlic Extracts Trigger Antioxidants in Cucumber

Abstract: Garlic has the charisma of a potent remedy and holds its repute of a therapeutic panacea since the dawn of civilization. An integrated approach was adopted to evaluate the genetic diversity among Chinese garlic cultivars for their antifungal potency as well as allicin content distribution and, furthermore; a bioassay was performed to study the bio-stimulation mechanism of aqueous garlic extracts (AGE) in the growth and physiology of cucumber (Cucumis sativus). Initially, 28 garlic cultivars were evaluated agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 69 publications
8
51
1
Order By: Relevance
“…Hayat et al . showed that aqueous garlic extract altered the defense mechanism of cucumber seedlings through the activation of ROS at mild concentrations29. However, in the present study, the ROS content may decrease in response to the down-regulation of the RBOH genes involved in ROS production (Supplementary Table S6), suggesting that ROS may not be the active signal in inducing tomato resistance under 0.21 mM DADS conditions.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Hayat et al . showed that aqueous garlic extract altered the defense mechanism of cucumber seedlings through the activation of ROS at mild concentrations29. However, in the present study, the ROS content may decrease in response to the down-regulation of the RBOH genes involved in ROS production (Supplementary Table S6), suggesting that ROS may not be the active signal in inducing tomato resistance under 0.21 mM DADS conditions.…”
Section: Discussioncontrasting
confidence: 54%
“…(2013) showed that the activities of CAT and POD in pepper were significantly enhanced when intercropping with garlic, while that of PPO was inhibited7. In addition, the activities of SOD, POD and CAT in cucumber ( Cucumis sativus ) leaves were also increased in response to aqueous garlic extracts at proper concentrations29. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Garlic cultivar G025 was obtained from the garlic germplasm unit, College of Horticulture, Northwest A&F University, China. The aqueous extract was prepared according to method previously described in our article [27]. Due modifications were made, however, according to the requirements of experiment.…”
Section: Preparation Of Garlic Extracts and Acetyl Salicylic Acid Solmentioning
confidence: 99%
“…However, less is understood about the possible biological activity of garlic-derived compounds on the growth and physiology of receiver plants, particularly their utility as growth promotors, or about priming inducer/stimulator needs. In our earlier studies, aqueous garlic extract (AGE) has been shown to alter the antioxidative response of cucumber seedlings, and this effect was observed to be concentration-dependent [27]. Moreover, tomato seedlings' growth in response to variable concentrations of AGE revealed significant results [28].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that garlic has strong antioxidant properties. It has also been found that raw garlic has more antioxidant activity than cooked garlic [29]. Anti-inflammatory and immune protection effects of garlic have also been demonstrated [30].…”
Section: Discussionmentioning
confidence: 96%